The impact of NAFTA Chapter XI on Mexico - Quintero Sánchez, A., Melgar Manzanilla, P., (Opción, 2019)
The purpose of this paper is to review the impact of NAFTA Chapter XIin Mexico, and determine if the expectations of national development have been reached.The analysis is made via two methods: legal-economic and theoretical-practical. Therefore, the influence of the treaty is determined both in Mexico´s regulatory framework and in its economy.Direct foreign investment does not necessarily lead to the national development and that NAFTA Chapter XI, despite all the changes in Mexico’s legal structure, has not contributed substantially to its development. This should be taken into consideration as a precedent for the Latin America countries.